TRANSFORMATION OF THE CONCEPT «TRAINING OF TEACHER-PHILOLOGIST»: A RETROSPECTIVE APPROACH - Гайдай, Ирина; Жалинского, Ирина; Хорош, Ольга (SWorldJournal, 2020)
This article analyzes the conceptual apparatus of the study, which allowed to distinguish such categories as: "teacher-philologist of dual profile", "teacher-philologist of general profile", "specialist of integrative profile", "related / related special